Factor Xa inhibits HMGB1-induced septic responses in human umbilical vein endothelial cells and in mice - Lee, Wonhwa; Ku, Sae-Kwang; Bae, Jong-Sup (Thrombosis and Haemostasis, 2014)
Nuclear DNA-binding protein high mobility group box 1 (HMGB1) acts as a late mediator of severe vascular inflammatory conditions, such as sepsis. Activated factor X (FXa) is an important player in the coagulation cascade responsible for thrombin generation, and it influences cell signalling in various cell types by activating protease-activated receptors (PARs). However, the effect of FXa on HMGB1-induced inflammatory response has not been studied. First, we addressed this issue by monitoring the effects of post-treatment with FXa on lipopolysaccharide (LPS)- and cecal ligation and puncture (CLP)-mediated release of HMGB1 and HMGB1-mediated regulation of pro-inflammatory responses in human umbilical vein endothelial cells (HUVECs) and septic mice. Post-treatment with FXa was found to suppress LPS-mediated release of HMGB1 and HMGB1-mediated cytoskeletal rearrangements. FXa also inhibited HMGB1-mediated hyperpermeability and leukocyte migration in septic mice. In addition, FXa inhibited the production of tumour necrosis factor-α and interleukin (IL)-1β. FXa also facilitated the downregulation of CLP-induced release of HMGB1, production of IL-6, and mortality. Collectively, these results suggest that FXa may be regarded as a candidate therapeutic agent for treating vascular inflammatory diseases by inhibiting the HMGB1 signalling pathway.
Keywords: FXa; HMGB1; vascular inflammation; sepsis